Team feel: An exploration of a group resonance-based intervention and relationships - Wolfe, Barat Jade (University of Ottawa (Canada), 2006)
The purpose of this study was to explore and document the process through which a team of athletes and coaches felt and attempted to learn and apply resonance in a group context throughout a season. Resonance is a process that allows people to identify how they want to feel, prepare to experience that desired 'feel,' recognize obstacles that prevent them from feeling the way they want, and reconnecting when they are disengaged (Newburg, 2006; Newburg et al., 2002). Sixteen synchronized swimmers, one head coach, and one assistant coach participated in a group resonance based intervention over the span of a four month competitive season. The results, which are presented as two narratives, suggest that a group resonance process is possible. However, participants must be prepared to take ownership of this process and engage in challenging, deliberate work to incorporate their individual desired feel and the desired feel of others in the everyday experiences of a competitive team. This story also indicates that unresolved conflict can be detrimental to (a) relationships between athletes and coach, (b) performance, and (c) how people want to feel in the context of their sport.
Keywords: Health Sciences, Recreation.